Candidemia in Cancer Patients: A Retrospective Analysis at a Cancer Center From 2001 to 2014. Issue 5 (September 2016) - Yacoub, Abraham Tareq; Moreland, Spencer; Jani, Devang; Nanjappa, Sowmya; Quilitz, Rod; Carraway, Stephanie; Sandin, Ramon L.; Greene, John N.
Abstract : Introduction: While the global epidemiology of candidemia has been studied in great detail, there are relatively few data available examining the effects of recent changes in antifungal treatment patterns on the susceptibility and species distribution patterns of Candida species. Likewise, there are relatively few data documenting improved outcomes in patients with candidemia. Materials and Methods: We reviewed the charts of all patients at our institution with one or more positive blood cultures for Candida species between January 1, 2001, and June 18, 2014. We first looked at the remaining set of 247 patients who met these criteria, followed by an isolated subset of 115 patients with hematologic malignancies (HMs). All patients were selected from the H. Lee Moffitt Cancer Center and Research Institute, Tampa, FL, based on positive Candida culture reports obtained from Moffitt's microbiology laboratories. From these reports, we obtained the patient name and medical record number, positive sample collection dates, number of positive culture days, species of Candida, and patient location in the hospital. We included positive samples taken from peripheral and central lines but excluded samples taken from catheter tips. Blood cultures were initially analyzed using either the Bactec or the BacT/Alert system. Cultures that were positive for yeasts were Gram-stained, and yeasts were cultured on Sabouraud dextrose agar and chocolate agar. Yeast species were tentatively classified by visual examination and conclusively identified using either the RapID YeastOne system or the Vitek 2 system. Drug susceptibilities were determined via serial dilutions using the TREK Sensititre YeastOne system. After data collection from the laboratory reports, we examined the patient's medical records and collected additional data points. Susceptibility data on fluconazole, amphotericin B, voriconazole, micafungin, 5-flucytosine, posaconazole, caspofungin, itraconazole, and anidulafungin were collected if available. We compared frequency of each Candida species overall as well as over different time intervals for all patients, those with only non-HMs, and those with only HMs. Results: The most prevalent infecting species overall was Candida albicans followed closely by Candida glabrata . The frequency of infection with other species, beginning with Candida krusei, was much lower. The most prevalent infecting species was C . albicans, which by itself represented a little less than half of all non-HM patients. Candida glabrata was once again the next most frequent species. The most prevalent infecting species for patients with HMs was C . glabrata followed by C. krusei, which together combined for more than half of infections. Candida albicans was not nearly as frequent in this group, and in fact was the least prevalent of the major species. When comparing the first 5 years with the last 5 years, the most prevalent species during both periods was C . glabrata, C . albicans, and Candida tropicalis with incidences falling substantially, whereas Candida parapsilosis incidences rose substantially. The prevalence of C . krusei also showed a moderate increase. There were no other Candida species between 2001 and 2006, further illustrating the shift that has occurred. Eleven deaths were deemed attributable to candidemia in comparison to 40 deaths deemed attributable to the underlying disease (malignancy, other infections, organ failure due to graft-versus-host disease, etc). Conclusions: Our data regarding breakthrough infections while on prophylactic antifungal treatment illustrate how most candidemias that breakthrough while on micafungin are C . parapsilosis and C . krusei . Further information is needed to determine how these trends might impact treatment recommendations for candidemia and to ensure optimal effectiveness in preventing and treating candidemia in patients with cancer.